Not All ENT Granulomas Are Wegener's - Keep Tuberculosis in Mind. - Pedro, B (2020)
Mycobacterium tuberculosis affects the middle ear in rare cases and is a challenging diagnosis. In this case, we present a 57-year-old patient diagnosed with anti-neutrophil cytoplasmic antibody (ANCA)-negative granulomatosis with polyangiitis (GPA) following a biopsy result of nasal granulomas, who was immediately started on immunosuppressive treatment. Years later, she developed progressive hypoacusis. Magnetic resonance imaging (MRI) revealed an extensive mass in the tympanic cavity extending to the mastoid. A biopsy of the mass was positive for Mycobacterium tuberculosis. Immunosuppressants were weaned and the patient was started on anti-tuberculous therapy with resolution of the complaints and findings. Tuberculous infections are difficult to diagnose and frequently mimic other illnesses, but in our case, we believe that an indolent tuberculous process was present from the beginning and evolved under immunosuppressive therapy. LEARNING POINTS: The differential diagnosis of rhinosinus granulomatous findings includes inflammatory and infectious diseases (for example, tuberculous infections), in addition to neoplasms, cocaine abuse and trauma.A comprehensive differential diagnosis list is essential to mitigate diagnostic errors, especially in patients where auto-immune studies are negative or there is any doubt in the diagnosis.Latent tuberculosis screening should be a concern for physicians treating patients with immunosuppressive therapy, especially in endemic countries.